Morphogenic and pathogenic variations in Gloeosporium ampelophagum - and CHANDER MOHAN, SAWROOP KUMAR, T.S. THIND (Indian Phytopathology, 2002)
Sixty two isolates of G. ampelophagum [Elsinoe ampelina] from various vineyards in the Indian Punjab were categorised into 3 distinct groups (GA I, GA II and GA III) based on morphological characters of the colonies (4 isolates were put into a miscellaneous category). Isolates of group GA I were predominant compared with isolates of the other 2 groups. When tested on potted grape plants as well as by the detached leaf technique under artificial epiphytotic conditions, group GA I isolates also appeared to be more pathogenic and aggressive with shorter incubation periods.